Surgical management with osteogenic distraction for midface hypoplasia in a specialized institute in Lima, Peru - Oré Acevedo, Juan Francisco (2025)
Background: Several patients with Crouzon, Apert, or Pfeiffer syndrome, or those with cleft lip and palate, exhibit growth alterations of the craniofacial bones, including midface hypoplasia and exophthalmos that necessitate surgical correction, which is not routinely performed. Currently, bone distraction provides a reliable method for midface advancement through gradual traction of the bone segment. Objective: To describe the outcomes of osteogenic distraction for the correction of midface hypoplasia in patients treated at a national children's hospital in Lima, Peru. Methods: A  review  of  medical  records  was  conducted  at  the  institution  to  identify  patients  who  underwent midfacial distraction surgery between 2016 and 2022. Results: We identified 22 patients who underwent bilateral midface osteogenic distraction, with a mean age of 15 years. The diagnoses were cleft lip and palate (72.7 %), Crouzon syndrome (22.7 %), and Apert syndrome  (4.5  %).  The  most  commonly  performed  procedure  was  modified  quadrangular  Le  Fort  II  distraction in 9 cases (40.9 %). Following surgery, correction of exophthalmos, increased projection of the inferior orbital rim along with the malar and upper jaw, enlargement of the nasopharyngeal space, and advancement of the upper dentition due to bone advancement were observed. Conclusion: The  application  of  bone  distraction  is  currently  the  gold  standard  technique  to  correct  anteroposterior  discrepancies  greater than 10 mm of the midface, as it improves exophthalmos, the projection of the malar and upper jaw, increases the nasopharyngeal space, and achieves advancement of the upper arch.